Implementasi Program Pertukaran Pemuda Antarnegara Pada Dinas Pemuda dan Olahraga Sumsel dalam Pengembangan Sumber Daya Manusia Tahun 2020-2021 - Ramdiastuti, Lucia Weny; Nengyanti, Nengyanti; Tahmrin, Husni (Universitas Indo Global Mandiri, 2024)
Based on Law Number 40 of 2009 concerning Youth, the youth category is 16 to 30 years old. In the 2021 BPS, the number of youths in South Sumatra reached 359,151. Youth development is carried out in order to improve the spirit of leadership, entrepreneurship, and youth pioneering so that, in the end, it can produce advanced youth, namely youth with character, capacity, and competitiveness (Heri, 2015). The purpose of this research is to explain the Implementation of the Inter-Country Youth Exchange Program at the South Sumatra Dispora related to HR Development as an effort to Build Youth Character in South Sumatra. The results showed that participants who received program benefits admitted that they did not receive optimal benefits. In addition, some parts of the activity did not run optimally because they were only virtual. The beneficiaries also stated that they could not accept the opportunity for internships. This is different from the beneficiaries of the program in the normal era. Another finding is that the PPAN program has not been optimally socialized in all districts and cities. A letter of notification regarding the PPAN program from the Ministry of Youth and Sports addressed to the Provincial Dispora, which was then forwarded to the district or city Dispora regarding the selection of the PPAN program, did not reach the sub district, village, or kelurahan. Because the district or city Dispora has not optimally escorted it to the sub-districts because there is no socialization budget yet.